1987
DOI: 10.1002/jso.2930360209
|View full text |Cite
|
Sign up to set email alerts
|

Management of endoscopically removed malignant colon polyps

Abstract: The medical records of 87 patients with 89 malignant colorectal polyps removed endoscopically between 1971 and 1983 were reviewed retrospectively. Fifty-five polyps contained carcinoma-in-situ. Four polyps had "pseudo-invasion" by displaced mucosal glands. Thirty polyps contained invasive carcinoma. No patients with carcinoma-in-situ or "pseudo-invasion" had either local residual disease or metastatic disease at the time of colectomy or which was detected during subsequent follow-up. Four patients (14%) with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In 23 series, [14][15][16][17][18][19][20][21][22][24][25][26][27]29,[31][32][33][34][35]38,[40][41][42] clinical or endoscopic follow-up data were available, ranging from 12 to 90 (median, 60) months, and accounting for 1,535 (80.1 percent) of the included polyps. Regarding endoscopic data, polyp site was clearly specified in 17 series, accounting for 1,461 polyps.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In 23 series, [14][15][16][17][18][19][20][21][22][24][25][26][27]29,[31][32][33][34][35]38,[40][41][42] clinical or endoscopic follow-up data were available, ranging from 12 to 90 (median, 60) months, and accounting for 1,535 (80.1 percent) of the included polyps. Regarding endoscopic data, polyp site was clearly specified in 17 series, accounting for 1,461 polyps.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Death because of surgical complications, inferred from 28 studies, was reported in 8 (0.8 percent) of 951 operated patients. [12][13][14][15][16][17][18][19][20][21][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42] …”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…By 1975 Wolff and Shinya (2), on the basis of the histopathological expertise of Riddell and Morson (J) and their already considerable experience of colonoscopic polypectomy, gave a 'seal of approval' co the principle of conservatism in the management of malignant polyps. Since then a large number of ocher clinical series have supported this approach (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), as have editorials (20,21) and review articles (15,22,23 ).…”
mentioning
confidence: 99%